2019
DOI: 10.29130/dubited.482651
|View full text |Cite
|
Sign up to set email alerts
|

Nesnelerin İnterneti Tabanlı Meteorolojik Veri Takip Sistemi

Abstract: Bu çalışmada, meteorolojik verilerin takibi, güneş ve rüzgar enerjisi açısından bölge potansiyelinin gerçek veriler ile saptanması, hava veya alternatif enerji sistemleri tahmin algoritmalarında kullanılmak üzere meteorolojik verilerin toplanması amaçlarıyla Kocaeli Üniversitesi Uzunçiftlik Nuh Çimento Meslek Yüksekokulu çatısına kurulan hava istasyonu ele alınmıştır. Kurulan hava istasyonu ile bölgenin global ışıma, rüzgar hızı, rüzgar yönü, sıcaklık ve nem verileri 32 bit Arduino Due mikrodenetleyici ile top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Another study conducted in 2019 focused on meteorological data tracking systems, and a tracking system was developed using the “Internet of Things” (IoT) method [ 30 ]. Meteorological data related to the meteorological data tracking station installed on the roof of Kocaeli University were made available to all users with Internet access by being transferred to the cloud environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted in 2019 focused on meteorological data tracking systems, and a tracking system was developed using the “Internet of Things” (IoT) method [ 30 ]. Meteorological data related to the meteorological data tracking station installed on the roof of Kocaeli University were made available to all users with Internet access by being transferred to the cloud environment.…”
Section: Discussionmentioning
confidence: 99%
“…The installed system monitored global radiation, wind speed, wind direction, temperature, and humidity data. According to the data obtained from the system, the monthly total radiation amounts per square meter were found to be 195 kWh m −2 , 174 kWh m −2 , 134 kWh m −2 , 86 kWh m −2 , and 79 kWh m −2 for August, September, October, November, and December, respectively [ 30 ]. As a result of this study, it was observed that the data could be tracked using the Internet.…”
Section: Discussionmentioning
confidence: 99%
“…The Internet of Things (IoT) has been called the next Industrial Revolution or the next evolution of the Internet. IoT can be defined as an advanced and effective solution for connecting objects to the internet and collecting data from objects and sharing them over a network [4]. The Internet of Things can be defined as a communication network in which physical objects are connected or with larger systems.…”
Section: Internet Of Thingsmentioning
confidence: 99%
“…Meteorological data tracking stations or automatic weather stations are used for monitoring weather conditions, weather forecasting, long-term monitoring of climate change, ensuring healthy growth in plants, providing a healthy working environment in industry, collecting meteorological data for energy systems, predicting natural events such as floods, landslides or avalanches. is used [4].…”
Section: Introductionmentioning
confidence: 99%
“…IoT is a technological paradigm that aims to increase the connectivity of everyday devices. Therefore, the growth and use of this type of technology will increase exponentially in the coming years due to its application in multiple fields [22]. In this study, an instant measurement device is designed for workplace health and safety.…”
Section: Internet Of Thingsmentioning
confidence: 99%